Nutritional practices of expectant mothers supported by a family health unit: an exploratory study - Palombarini, Aline Fernanda [UNESP]; Malta, Maíra Barreto [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP]; Carvalhaes, Maria Antonieta de Barros Leite [UNESP]; Benício, Maria Helena D'Aquino [UNESP]; Tonete, Vera Lúcia Pamplona [UNESP] (GN1 Sistemas e Publicacoes, 2014)
Aim: to identify the concepts regarding dietary practices among low income expectant mothers, and to understand the subjective aspects involved on their daily dietary practices. Method: this is an exploratory study, based on the theoretical reference of the Comprehensive Sociology of Everyday Life, performed with twelve pregnant women supported in a family health unit. The data was collected through semi-structured interviews, and treated according to the method of content analysis, using the thematic approach. Results: for the expectant mothers, their diet must be healthy, paying attention to its composition and schedule, however that is not always possible. They are given information and start having better nutrition during pre-natal care, but on the other hand, they need support from health services when facing difficulties. Discussion: the influence of life context was confirmed over the nutrition of expecting mothers, as well as the relevance of individual discipline and willpower towards a healthy nutrition. Conclusion: the adequate nutritional intervention must consider subjective factors that influence the way pregnant mothers have their diet and have their dietary choices.
Keywords: Pregnancy; Feeding; Family health